Penelitian Mengenai Metode Steganografi Least Significant Bit - Ivan Jonathan; Albert Yeusiawan Haryono; Kevin Leonardi (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
In today's technological era, the concealment of sensitive information is the concern of many people. Because the information is often shared and discussed through a very commonly used communication medium. Steganography is one technique to hide a secret message into a file that has a larger size. In this paper, we will discuss the methods that can be used in steganography, especially the method of Least Significant Bit. Keywords: Steganography, Data Hiding, Steganography Algorithm, Least Significant Bit.